Investigation of the mechanical and strength properties of the mortar barrel made of different composite materials - Pihtili, Hasim; Ulutas, Melih (Korean Soc Mechanical Engineers, 2022)
This study was conducted on mortar barrels, manufactured from different composite materials to replace the 120-mm mortar barrel, which is currently used in the defense industry. Kevlar/epoxy and glass/epoxy composite materials were used in the study. In this respect, the deformation, pressure, lifespan and flow analyses of the barrel were conducted and the mechanical and strength properties between two different composite mortar barrels were compared. The SolidWorks program was used in order to obtain a solid modeling. The resulting data were transferred to the ANSYS program for static and dynamic analyses and the necessary square mesh operations were performed and the results were transformed into graphics using the finite elements method.
Keywords: Mortar; Barrel; Composite material; Firearms